2013
DOI: 10.1002/anie.201307029
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Two‐Dimensional Supramolecular Polymers by Amphiphilic Pyrene Oligomers

Abstract: Reading the bands: Amphiphilic pyrene trimers self-assemble into two-dimensional, supramolecular polymers in aqueous medium. Folding and aggregation processes are accompanied by simultaneous development of J- and H-bands and significant changes in the fluorescence properties. The formation of sheet-like nano-structures is confirmed by AFM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 101 publications
(92 reference statements)
5
95
0
3
Order By: Relevance
“…Haner et al reported nanosheet formation with the pyrene unit. 35 Recently, we have discovered that the polymer, which was prepared from azide and alkyne-terminated tetra(ethylene glycol)-substituted phenyl-capped bithiophene derivatives by Cu-catalyzed Huisgen cycloaddition reaction, 36 could selfassemble into the nanosheet through polymer folding in an organic solvent. 37 We called our nanosheets "thiophene nanosheets" because they are 2D crystals of the thiophene units sandwiched by ethylene glycol layers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Haner et al reported nanosheet formation with the pyrene unit. 35 Recently, we have discovered that the polymer, which was prepared from azide and alkyne-terminated tetra(ethylene glycol)-substituted phenyl-capped bithiophene derivatives by Cu-catalyzed Huisgen cycloaddition reaction, 36 could selfassemble into the nanosheet through polymer folding in an organic solvent. 37 We called our nanosheets "thiophene nanosheets" because they are 2D crystals of the thiophene units sandwiched by ethylene glycol layers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1) are some of the most widely studied organic chromophores [4952]. Moreover, we have reported on the aggregation and stacking properties of 1,8- and 1,6-dialkynylpyrene [5354]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, as we synthesized that the bulk junction at 8 position exerts steric effect on the rotational motion of the phenyl ring, such effect was originated from the propeller-shaped TPA core and methyl acrylate groups with strong aggregation ability. [53,54] From emission spectrum (Fig. 1b).…”
Section: Design and Synthesis Of Target Moleculesmentioning
confidence: 99%